Participatory Variety Testing to Replace Old Mega Rice Varieties with Newly Developed Superior Varieties in Bangladesh - Hossain, Mohammad; Islam, Mohammad; Biswas, Partha Sarathi (MDPI, 2022)
The Bangladesh Rice Research Institute (BRRI) has released more than 100 inbred rice varieties. Still, an old mega variety BRRI dhan28 dominates the farmers’ fields during the dry winter (Boro season: November–June) season. This variety is very susceptible to different diseases and insects, causing lower yield performance than its potential. To replace this variety, current on-farm research was planned to evaluate the newly developed four superior rice varieties: BRRI dhan58, BRRI dhan63, BRRI dhan67, and BRRI dhan74 during Boro season in 2017 and 2018. The objective was to create data and popularize new varieties among farmers all over the country. We conducted 15 on-farm trials with farmers’ active participation at Senbag, Fulgazi, and Mirsarai Upazila of Noakhali, Feni, and Chattogram districts, respectively, in Bangladesh. The results demonstrate that BRRI dhan74 produced the highest grain yield among the tested varieties, followed by BRRI dhan67, BRRI dhan63, and BRRI dhan58, while BRRI dhan28 produced the lowest. However, BRRI dhan67 obtained the highest preference scores from the farmers and extension personnel due to its medium and slender grains, shorter growth duration, resistance to lodging, less disease, and less insect invasion. Moreover, stability indices for yield revealed that BRRI dhan67 was the most stable, adaptive, and appropriate variety, followed by BRRI dhan74, across the locations. Farmers showed keen interest to grow BRRI dhan67 by themselves instead of BRRI dhan28 all over the study locations. The neighboring farmers also expressed their curiosity about cultivating BRRI dhan67 over BRRI dhan28 by collecting seeds from the participating farmers. Thus, BRRI dhan67 could be a perfect replacement for BRRI dhan28. However, conducting participatory varietal evaluation trials across the agroecological zones of the country is recommended to validate the results of this study.